The Communication Patterns of Leadership in Improving Work Ethic of Lecturer and Staff in Asahan University (Islamic Communication Perspective) - Dailami Dailami; Syukur Kholil; Lahmuddin Lubis (Budapest International Research and Critics University, 2020)
This study aims to analyze the communication patterns of leadership in improving work ethic of lecturer and staff, the implementation of leadership communication patterns to the principles of Islamic communication and to identify various barriers occurring at Asahan University. The research method used in this study is a descriptive method through a qualitative approach, by observing the state of the subject or object of research at the time of the study based on the events that are seen. The results of research carried out show the communication patterns of leadership in improving work ethic of lecturer and staff through vertical patterns, horizontal patterns and diagonal patterns. Whereas the implementation of Islamic communication Principles at Asahan University are Qaulan Sadīdā, Maīysūrā Qaulan, Ma'rūfā Qaulan, Layyinā Qaulan, Karīma Qaulan and Balighā Qaulan. Barriers in improving work ethic of lecturer and staff include mental attitude, primordial relation, welfare levels and improper placement of work fields.